Contextualizing Scenarios to Explore Social-Ecological Futures: A Three Step Participatory Case Study for the Humboldt Current Upwelling System - Garteizgogeascoa, María; Kluger, Lotta C.; Gonzales, Isabel E.; Damonte, Gerardo; Flitner, Michael (Frontiers in Marine Science, 2020)
In the face of global change, the exploration of possible futures of marine social-ecological systems (MSES) becomes increasingly important. A variety of models aims at improving our understanding of ecosystem dynamics and complexities by assessing how systems react to internal and external drivers of change. However, these models are often built from a natural-science perspective through a reductionist and top-down knowledge production process that does not engage with the interests, concerns and knowledge of stakeholders. Our work explores different futures of the Peruvian MSES tied to the Humboldt Current Upwelling System (HCUS) through a sequential integrative participatory scenario process. The methodology used opens novel ways to explore, at different contextual levels, the uncertainties of the future and, in doing so, to include diverging world views of different actors. This approach implies a broader social processing of scientific projections about the future and encourages the articulation of different notions of sustainability. We thereby contribute to current scientific discussions on scenario planning in MSES by exploring potential futures through the analysis of narratives, a process that helps to identify plausible future development pathways that can inform different types of ecosystem modelling or policy making.